Battery Loss Minimization Using Dynamic Programming for Energy Management in EVs - Bui, Dang Quang; Ta, Cao Minh (Old Journal, 2020)
Almost all EVs use battery as the main energy storage system. Therefore, extending the battery’s life is a particularly important area in Energy Management for EVs beside extending the vehicles’ running distance. Battery’s loss is one of the reasons to reduce the battery’s lifetime. Moreover, the loss leads to a reduction in running distance of EVs. Hybrid Energy Store System (using battery and super capacitor), which is used in this paper, is a good solution in Energy Management for EVs. The authors use Dynamic Programming to minimize the battery loss and the results can be used as a benchmark for comparison with the real-time EV operation in ECE driving cycles.